Stages of reconstruction and renewal of Ukraine’s infrastructure in the war and post-war period, taking into account experience and security - Ugnenko, Evgeniya; Shevchenko, Anna; Shevchenko, Oleksander (International Conference “Environmental Engineering”, 2023)
The article provides statistical data on the damage to critical and road infrastructure as a result of the armed aggression of the Russian Federation against Ukraine. Also, taking into account the constant missile attacks and destruction make it impossible to restore and operate sections and systems of communication routes, which leads to greater wear and tear and the inability to use them as intended. The purpose of this research is the analysis of the system of communication routes and the development of the stages of restoration of their operation with the calculation of the estimated need for financing. The article presents the possibility of harmonizing regulatory, legal and organizational aspects of the transport industry of Ukraine with EU countries to meet the needs of the population in transportation and ensure the development of the country’s economy by changing approaches to the formation of transport and logistics solutions and the development of modern transport infrastructure. What the stages of recovery involve: short-term (at the stage of martial law); medium term (restoration and restart of systems); modernization (deepening the integration of the national transport network with the EU transport network).